Effect of Mn and Zn doping on natural resonance frequency of strontium U-type hexaferrite and its performance as electromagnetic wave absorbers - Ismail, Ismayadi; Muhammad Zulkimi, Muhammad Misbah; Azis, Raba’ah Syahidah; Mustaffa, Muhammad Syazwan; Hamidon, Mohd Nizar; Ertugrul, Mehmet; Yesilbag, Yasar Ozkan; Tuzluca, Fatma Nur; Hasan, Intan Helina; Ozturk, Gokhan; Hasar, Ugur Cem (Elsevier, 2022)
In the present work, substitution of strontium U-type hexaferrite with the composition of Sr4Mn2-xZnxFe36O60 (x = 0.5,0.6,0.8, and 1.0) was prepared via high energy ball milling (HEBM) and sintered at 1100 °C. The phase, microstructure, magnetic, dielectric and electromagnetic wave absorbing properties of U-type strontium hexaferrite composites were measured using XRD, FESEM, and Vector Network Analyzer in the frequency range of 8–18 GHz (X-band and Ku-band). MnZn doping was found to shift the natural resonance of the materials by affecting its magnetocrystalline anisotropy. The reflection loss (RL) indicated that the composite possessed good microwave-absorbing properties with U-type strontium hexaferrite ( Sr4Mn2-xZnxFe36O60) of x = 0.8 resulted in high minimum RL value for all thickness of 1 mm and two peaks at approximately − 32.50 and − 41.50 dB at 14.00 and 15.60 GHz, with bandwidth of 0.60 and 0.80 GHz for losses less than − 10 dB.